Pineal Gland—A Spiritual Third Eye: An Odyssey of Antiquity to Modern Chronomedicine - Raj Kumar; Arushi Kumar; Jayesh Sardhara (Indian Journal of Neurosurgery)
Pineal gland or “spiritual third eye” is regarded as the gateway of spiritual life as per ancient concepts about the soul. Recently, modern neuroscience has proven that pineal gland is not only the melatonin-secreting neuroendocrine organ which controls the circardian rhythm, but it also has mystical and energetic associations with spirituality. It acts as a tremendous coordinator between molecular, hormonal, physiological, and chemical rhythmic orchestra. Thus, in this article, by highlighting the relation between ancient Indian methodology and modern chronomedicine, the author describes the odyssey of antiquity to modern science.